(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
This study aims to trace the magnitude of the number of publications in the field of Responsible Leadership. This study also aims to gauge the Annual Scientific production, most relevant contributors in the field of Responsible Leadership with their citations, Author Productivity through Lotka’s Law, most relevant journals, Journal production over time, Affiliation of the country, Corresponding author's country, Keywords used in the publications with their frequency, trendy topics, collaboration network of the authors, co-citation network and Factorial analysis. The outcomes of the study not only contribute to the existing literature but also prove to be a great help in doing a Systematic Literature Review. Future research in the field will also be easy to decide with the help of this study.